Penerapan Model Pembelajaran Kooperatif Tipe GI (Group Investigation) untuk Meningkatkan Motivasi dan Prestasi Belajar Pada Pembelajaran Sejarah Siswa Kelas X TKR 2 SMK Negeri 2 Baubau Tahun Pelajaran 2018/2019 - La Jauhari (Jurnal Akademik FKIP Unidayan, 2020)
This study aims to improve learning motivation and achievement of learning history in Indonesia through the Group Investigation method in class X TKR 2 students of SMK Negeri 2 Baubau in 2018/2019 Academic Year This research was conducted in class X TKR 2 SMK Negeri 2 Baubau in 2018/2019 Academic Year with 32 students consisting of 27 male students and 5 female students. This research is a class action research (CAR) with the steps of the activities including planning, action, observation, analysis and reflection which is one cycle, this research was conducted in 2 cycles. Data collection techniques are done using observations/observations, questionnaires and tests. The data analysis technique used is quantitative description and qualitative description by comparing initial conditions with conditions at the end of each cycle. The results showed that the learning process using the Group Investigation method can improve learning motivation and achievement of learning outcomes in Indonesian History. In the Pre cycle the motivation to learn the history of Indonesia an average of 25.88 or 49.76% and the achievement of student learning outcomes that achieve complete value. KKM (Minimum completeness criteria) 2.67 are 10 students (31.3%) and students whose grades are not yet completed <KKM (Minimum completeness criteria) there are 22 students (68.7%), in the first cycle learning motivation of Indonesian history increased to an average of 36.53 or 70.25% and student achievement that achieves grades. KKM (Minimum completeness criteria) increased to 17 students (53.1%), while students who have not completed <KKM (Minimum completeness criteria) there were 15 students (46.9%) while in the second cycle there was a significant increase namely historical learning motivation Indonesia has an average of 40.19 or 77.28% and student achievement is achieving grades. KKM (Minimum completeness criteria) 2.67 increased to 29 students (90.6%) while students who have not completed or <KKM (Minimum completeness criteria) 2.67 there are 3 students (9.3%).